A Study on Consumer Behaviour: Transition from Traditional Shopping to Online Shopping During the COVID-19 Pandemic - Dwi Nita Aryani; Rajesh Kumar Nair; Dana Xing Yue Hoo; Daisy Kee Mui Hung; Deborah Hong Ru Lim; Dharaniya A/P Ravi Chandran; Wei Ping Chew; Amey Desai (AIBPM Publisher, 2021)
This study aims to investigate Malaysian and Indian consumers’ preferred ways of shopping, the reasons behind their choices, and problems of transactions they faced during the pandemic. Data were primarily collected through a survey distributed to 200 respondents. The study concluded that it is unlikely for online shopping to replace traditional shopping as many consumers remain value physical examination of the products prior to purchase. However, many have opted for online shopping for its various advantages. Regardless of which method of shopping, respondents face similar problems in their transactions. The findings of this study may serve as a guideline for businesses to integrate into online shopping platforms for potential future development.